Comment on the article entitled ‘Study of public human tissue resource bank for research purposes-An attempt to establish a surgically removed tonsil tissue bank at National Children's Hospital-’ in Tissue Culture Research Communications (19: 163-183, 2000), focusing on procedures of informed consent with tissue donor - Shirai, Yasuko (TISSUE CULTURE RESEARCH COMMUNICATIONS, 2001)
Personal comments were described about the procedures of informed consent in the process of donation to human, tissue bank in National Children's Hospital, based on legal, ethical, psychological, and social considerations about genetic diagnosis and counseling for muscular dystrophy. There are obvious differences between 'to receive medical care' and 'to be a subject of medical studies', since the former pursues patient's best interest but the latter aims scientific progress in medicine. In the present study and expected other human tissue banks, the samples are originally removed by the purpose of medical care. The authors of the original paper are required to explain an appropriateness of another standard for donation of human tissues.